Hubungan Self Efficacy terhadap Kepatuhan dalam Pembatasan Asupan Cairan pada Pasien Gagal Ginjal Kronik di Rsud Dr M Yunus Bengkulu - Andri Kusuma Wijaya; Fatsiwi Nunik Andari; Nurhayati Nurhayati (Universitas Malahayati Lampung, 2023)
ABSTRACT Chronic kidney failure is a form of impaired kidney function where this disorder occurs progressively and irreversibly, this condition causes the inability of body functions to maintain fluid and electrolyte balance which eventually causes clinical manifestations such as uremia. Another impact that arises as a result of chronic kidney failure in this case is a decrease in the ability of kidney function to dilute urine normally or a decrease in the ability to concentrate urine, resulting in edema. The result of edema is the occurrence of weight gain between two hemodialysis times so that client compliance is required in limiting fluid intake. Compliance with fluid intake restrictions is something that needs to be considered in clients with chronic kidney failure. There are several factors that can affect the limitation of fluid intake in patients with chronic kidney failure, one of which is self-efficacy where this action is the ability of the client to be able to carry out a diet so that it reduces the amount of fluid in the client's body. The purpose of this study is to determine the distribution of respondents' characteristics based on the level of fluid restriction compliance category, self-efficacy category and the relationship between self-efficacy and compliance in limiting fluid intake of clients with chronic kidney failure RSUD Dr M Yunus Hospital Bengkulu. This research is a quantitative study using a cross-sectional research design which will later be used to see the results of the relationship between self-efficacy and compliance in limiting fluid intake to clients with chronic kidney failure RSUD Dr M Yunus Hospital Bengkulu. The results of the univariate analysis of this study revealed that most of the respondents were based on compliance category where most of the clients complied as many as 61 clients (67.8%), while 29 clients (32.2%) did not comply. While the results of the characteristics of respondents based on the self-efficacy category, most of the self-efficacy clients in the moderate category were 51 clients (56.7%), for self-efficacy in the good category with 23 clients (25.6%) while 16 clients (17.8%) with the category poor self-efficacy. The results of the bivariate analysis of this study using the chi-square test statistical test obtained P value = 0.001 0.05. The conclusion of this study is that there is a relationship between self-efficacy and compliance in limiting fluid intake for clients with chronic kidney failure RSUD Dr M Yunus Hospital Bengkulu. Keywords: Compliance, Fluid, Self Efficacy ABSTRAK Gagal ginjal kronik merupakan suatu bentuk terganggunya fungsi ginjal dimana gangguan ini terjadi secara progresif serta irreversible, kondisi ini menyebabkan ketidakmampuan fungsi tubuh untuk mempertahankan keseimbangan cairan dan elektrolit yang akhirnya menimbulkan manifestasi klinis seperti uremia. Dampak lain yang dimunculkan akibat dari gagal ginjal kronik dalam hal ini menurunya kemampuan fungsi ginjal mengencerkan urine secara normal atau penurunan kemampuan mengkosentrasikan urine sehingga terjadinya edema. Akibat dari edema ialah terjadinya penambahan berat badan diantara dua waktu hemodialisa sehingga diperlukan kepatuhan klien dalam melakukan pembatasan asupan cairan. Kepatuhan dalam pembatasan asupan cairan merupakan hal yang perlu diperhatikan pada klien gagal ginjal kronik. Adapun Beberapa Faktor yang dapat mempengaruhi pembatasan asupan cairan pasien gagal ginjal kronik ialah salah satunya self efficacy dimana tindakan ini merupakan kemampuan yang dimiliki oleh diri klien untuk mampu melaksanakan diet sehingga menurunkan jumlah cairan yang ada di tubuh Klien Adapun tujuan dari penelitian ini diketahui distribusi karateristik responden berdasarkan tingkat kategori kepatuhan pembatasan cairan, kategori self efficacy serta diketahui hubungan self efficacy terhadap kepatuhan dalam pembatasan asupan cairan klien gagal ginjal kronik di RSUD Dr M Yunus Bengkulu. Penelitian yang dilakukan ini merupakan penelitian kuantitatif dengan menggunakan rancangan penelitian cross sectional dimana nantinya digunakan untuk melihat hasil dari hubungan antara self efficacy dengan kepatuhan dalam pembatasan asupan cairan pada klien gagal ginjal kronik di RSUD Dr M Yunus Bengkulu. Hasil dari analisis univariat dari peneltian ini diketahui sebagian besar responden berdasarkan kategori kepatuhan dimana sebagian besar klien patuh sebanyak 61 klien (67,8 %), sedangkan 29 klien (32,2 %) tidak patuh. Sementara hasil karateristik responden berdasarkan kategori self efficacy sebagian besar klien self efficacy dengan kategori sedang 51 klien (56,7%), untuk self efficacy kategori baik dengan 23 klien (25,6%) sementara 16 klien(17,8%) dengan kategori self efficacy buruk. Hasil analisis bivariat dari penelitian ini dengan menggunakan uji statistic uji chi-square didapatkan P value= 0,001 0,05. Kesimpulan hasil dari penelitian ini ialah ada hubungan antara self efficacy dengan kepatuhan dalam pembatasan asupan cairan klien gagal ginjal kronik di RSUD Dr M Yunus Bengkulu Kata Kunci: Kepatuhan, Cairan, Self Efficacy